Serum human trophoblast cell surface antigen and T-box protein 5 levels play a role in predicting adverse pregnancy outcomes in eclampsia: Trop-2 and TBX5 in predicting adverse pregnancy outcomes in eclampsia - Li, Yao; Huang, Sutong; Xuan, Yan; Shen, Hao; Zhang, Weiwei; Li, Jia (Journal of Medical Biochemistry, 2025)
Objective: The levels of human trophoblast surface antigen (Trop-2) and T-box protein 5 (TBX5) in the serum of patients with preeclampsia were detected, and their value in predicting adverse pregnancy outcomes was analyzed. Methods: A total of 196 pregnant women with preeclampsia who underwent prenatal examinations and delivered in our hospital from October 2021 to September 2024, as well as 196 healthy pregnant women, were selected as the eclampsia group and the control group, respectively. The 196 pregnant women with preeclampsia were divided into two groups according to their pregnancy outcome: the adverse outcome group and the good outcome group. Using the enzyme-linked immunosorbent assay (ELISA), the levels of serum Trop-2 and TBX5 were measured. Using multivariate logistic regression analysis, the factors impacting the various pregnancy outcomes of preeclamptic pregnant women were examined. Results: Compared with control group, the serum TBX5 levels in the eclampsia group (20.86±6.45 µg/L vs. 15.34±5.07 µg/L), as well as diastolic blood pressure, FBG, 24-hour urine protein, TG, systolic blood pressure and TC, were significantly greater. The levels of Trop-2 [(5.46±1.72) µg/L vs. (7.37±2.08) µg/L]. The total incidences of preterm infants, fetal distress, placental abruption and adverse pregnancy outcomes in the eclampsia group were significantly greater than those in the control group (P<0.05). The serum TBX5 level in the adverse outcome group [(23.01±6.66) µg/L vs. (19.53±6.32) µg/L], as well as diastolic blood pressure, FBG, 24-hour urine protein, TG, systolic blood pressure, and TC, were significantly greater than those in the good outcome group. The levels of Trop-2 [(4.90±1.61) µg/L vs. (5.81±1.79) µg/L] and HDL-C decreased significantly (P<0.05); Trop-2 [OR 95% CI: 0.38 (0.28,0.53)], TBX5 [OR 95% CI: 3.89 (1.88,8.04)] and 24-hour urine protein [OR: 3.14 (1.82,5.42)] were influencing factors for the pregnancy outcome of pregnant women with preeclampsia (P<0.05); and the AUCs of serum Trop-2, TBX5 and their combination in predicting the pregnancy outcome of pregnant women with preeclampsia were 0.79, 0.76 and 0.90, respectively. The combined prediction of the two had a greater predictive value than did Trop-2 or TBX5 alone (all P<0.05). Conclusion: The serum Trop-2 level of pregnant women with preeclampsia is abnormally low, and the TBX5 level is abnormally high. The combination of the two can be used as a biological indicator for evaluating adverse pregnancy outcomes.